Effects of combined oral contraceptive pills on thyroid function tests in Mosul City - Mohammed Daood Mahmood; Wahda B. Al-Youzbaki (University of Mosul, 2011)
Background: There are very little studies to determine the effects of combined oral contraceptive pills (COCPs) on thyroid function tests in hormonal contraceptive users at least in our locality. Objective: To evaluate the effects of COCPs on serum level of thyroid stimulating hormone (TSH) , free triiodothyronine (FT٣) and free tetraiodothyronine (thyroxine) (FT٤) and in relation to the duration of their usage in Mosul City. Design: A case control study. Subject & Methods: This study was conducted during the period from September ٢٠٠٨ to March ٢٠٠٩. A total of ٧٨ healthy married women , age range between ١٩-٣٥ years, from those who were attending AL-Batool and AL-Khansa Family Planning Centers in Mosul, who were taking Microgynon tablets which are one of monophasic, second generation combined oral contraceptive pills (COCPs) (contain ٠.٠٣ mg of ethinyl estradiol and ٠.١٥ mg levonorgestrel) (N=٤٨) for a period ranged between ٣ months to ٥ years and these were considered the users group. Other ٤٠ healthy married women who did not use any hormonal contraceptives and were drawn from the same population and matched for age, body mass index (BMI) with the users group and they were considered as the non users groups. Blood samples (٥ml) were obtained from COCPs users and non-user groups. The sera obtained from the blood samples were used for the estimation of serum TSH, FT٣, FT٤ using Menividus analytic device. Results: This study revealed non significant differences in TSH , FT٣ and FT٤ serum levels between COCPs users and non users and no correlation between serum TSH, FT٣ and FT٤ levels and duration of hormonal contraceptives usage. Conclusion: This study supported that the free thyroid hormone tests are the tests of choice in assessing thyroid function of women taking COCPs and concluded that COCPs can be regarded as a safe drugs in women using these types of hormonal as far as thyroid function is concerned.